Studies on the growth and development of Nerine bowdenii W. Watson (Amaryllidaceae) - Theron, K. I. (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. Agric.) -- University of Stellenbosch, 1993.